Testing the cultural group selection hypothesis in Northern Ghana and Oaxaca - Acedo-Carmona, Cristina; Gomila Benejam, Antoni (Cambridge University Press, 2016)
We examine the cultural group selection (CGS) hypothesis in light of our fieldwork in Northern Ghana and Oaxaca, highly multiethnic regions. Our evidence fails to corroborate two central predictions of the hypothesis: that the cultural group is the unit of evolution, and that cultural homogenization is to be expected as the outcome of a selective process.
Comentario incluido en: Richerson P, Baldini R, Bell AV, et al. Cultural group selection plays an essential role in explaining human cooperation: A sketch of the evidence. Behavioral and Brain Sciences. 2016;39:e30. doi:10.1017/S0140525X1400106X
Keywords: Identidad colectiva; Identidad étnica; competition; culture; evolution; group selection; heritable variation; institutions; norms